Electroencephalography as a Prognostic Tool after Cardiac Arrest - Westhall, Erik (Seminars in Neurology, 2017)
Multiple prognostic tools are used to evaluate prognosis for comatose survivors resuscitated after cardiac arrest (CA). Next to the clinical neurologic examination, electroencephalography (EEG) is the most commonly used method to assess prognosis. However, the reliability of EEG has been limited by varying classification systems, interrater variability, and the influence of sedation. Another important purpose of EEG is to evaluate clinical and subclinical seizures. The American Clinical Neurophysiology Society (ACNS) recently proposed a standardized EEG terminology for critically ill patients suitable for use after CA. Standardization is essential for reproducibility, meta-analyses, and clinical application of study results. Electrophysiological recovery or failure of recovery can be monitored with EEG during the first few days after CA. Electroencephalographic patterns highly predictive of poor outcome, such as generalized suppression and burst suppression, will be discussed in relation to the ACNS terminology and the time point after CA. The author focuses on the prognostic value of EEG after CA, using both continuous EEG monitoring and routine EEG. The evidence for predicting poor as well as good prognosis will be reviewed and practical suggestions are provided.
Keywords: Electroencephalography; prognosis; cardiac arrest; brain injury; outcome